Kerancuan Berpikir: Propaganda Publik Media Pro-Ukraina Dalam Situasi Perang Rusia-Ukraina 2022 - Edy Syahputra Sihombing; Maria Evangelina Maria Evangelina (Sapientia Humana: Jurnal Sosial Humaniora, 2022)
After the Russian invasion of Ukraine began in February 2022, the intertwined conflict between these two countries has provoked a ripple effect on public discourses across social media. In reality, the dynamics of the public narrative on the internet have provided a chance for political actors to create disinformation. Although Ukraine is the victim of the aggression, Ukrainian media' and politicians' response by constructing public propaganda and distorting the reality sparks various controversies for all social media users and other observers. A qualitative approach was used in this study with a review literature design. This study attempts to identify the main reasons behind the tendency toward Ukraine propaganda by justifying their action to disseminate misleading information and defy the truth in covering this case of an unjust war. Here it shows the fulfilled indicators of logical fallacies which have led the users to illogical sentiment entrenched in their interactions within the media plata form. The contribution of this study is an affirmation of the importance of critical thinking in the science of reason related to media literacy.